2023
DOI: 10.1371/journal.pone.0281375
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of adaptive to innate immune cells differs between genders and associates with improved prognosis and response to immunotherapy

Abstract: Immunotherapy has revolutionised cancer treatment. However, not all cancer patients benefit, and current stratification strategies based primarily on PD1 status and mutation burden are far from perfect. We hypothesised that high activation of an innate response relative to the adaptive response may prevent proper tumour neoantigen identification and decrease the specific anticancer response, both in the presence and absence of immunotherapy. To investigate this, we obtained transcriptomic data from three large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have also found a high level of variation between tumors and the tumor microenvironment between men and women 41 . However, we do not nd this difference between men and women, when we stratify based on BMI.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have also found a high level of variation between tumors and the tumor microenvironment between men and women 41 . However, we do not nd this difference between men and women, when we stratify based on BMI.…”
Section: Discussionmentioning
confidence: 92%
“…Next, we investigated the composition of in ltrating immune cells using the ratio of adaptive to innate immune cells (A/I ratio). We have previously shown that within tumors the A/I ratio is associated with improved survival 41 . Here, we found that in younger patients with small tumors, obese patients had a higher A/I ratio relative to non-obese patients (P = 0.041) (Fig.…”
Section: Small Tumors In Patients With High Bmi Show Unique Immune Pr...mentioning
confidence: 99%
“…Moreover, the concentration of adaptive immune cells relative to innate immune cells is variable across genders, further complicating the universality of immune-based cancer interventions. 103,104 Despite the complex biochemical signals and biophysical properties, T cell-based therapy remains a promising area of interest, especially compared to components of the innate immune response that have more varied effects on tumors. Such evidence indicates that CD8+ and CD4+ T cells are an important and effective component of the adaptive immune response to tumor cells, with recent efforts working to overcome limitations on their effectiveness.…”
Section: Immune Cell Recruitment To the Tmementioning
confidence: 99%
“…Bladder cancer (BC) is the second most prevalent neoplasm of the urinary tract, with an estimated US prevalence of a million cases and an alarming recurrence rate of 75-80% after initial transurethral resection of exophytic tumor (TURBT) [1]. The average age at onset of BC is 74 years [2] with a fourfold higher prevalence of BC in males compared to females [3].…”
Section: Introductionmentioning
confidence: 99%
“…The interplay of innate and adaptive immune cells between genders potentially influences BC prevalence, prognosis, and response to immunotherapy, which underscores the necessity for tailored treatment approaches [3]. A lower BC prevalence in females [4] may be mechanistically linked to the antitumor effect triggered by recurrent stimulation of innate immune cells by bacteriuria [5] and the resultant urothelial exfoliation may be inadvertently getting rid of [6] precancerous urothelium cells in females.…”
Section: Introductionmentioning
confidence: 99%